2017
DOI: 10.1101/168336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AKT isoforms have distinct hippocampal expression and roles in synaptic plasticity

Abstract: 13AKT is a kinase that regulates numerous cellular processes in the brain and mutations in AKT 14 are known to affect brain function. AKT is indirectly implicated in synaptic plasticity, but its direct 15 role has not been studied. Moreover, three highly related AKT isoforms are expressed in the 16 brain, but their individual roles are poorly understood. We find that each AKT isoform has a 17 unique expression pattern in the hippocampus, with AKT1 and AKT3 primarily in neurons but 18 displaying local differenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 50 publications
7
42
0
Order By: Relevance
“…The p110 subunit of PI3K converts phosphatidylinositol (3,4)-bisphosphate into phosphatidylinositol (3,4,5)-trisphosphate (PIP 3 ), leading to activation of the AKT family of serine/threonine kinase AKT1 and AKT3 isoforms in neurons, and AKT2 mostly in astrocytes. 23,24 AKT1 interacts with the pleckstrin homology domain of PIP 3 that enables phosphoinositide- dependent protein kinase 1 to phosphorylate threonine 308/309/305 residues of AKT1. The full activation of AKT1 requires phosphorylation of serine 473/474/472, respectively, by the mammalian target for rapamycin complex 2.…”
Section: Discussionmentioning
confidence: 99%
“…The p110 subunit of PI3K converts phosphatidylinositol (3,4)-bisphosphate into phosphatidylinositol (3,4,5)-trisphosphate (PIP 3 ), leading to activation of the AKT family of serine/threonine kinase AKT1 and AKT3 isoforms in neurons, and AKT2 mostly in astrocytes. 23,24 AKT1 interacts with the pleckstrin homology domain of PIP 3 that enables phosphoinositide- dependent protein kinase 1 to phosphorylate threonine 308/309/305 residues of AKT1. The full activation of AKT1 requires phosphorylation of serine 473/474/472, respectively, by the mammalian target for rapamycin complex 2.…”
Section: Discussionmentioning
confidence: 99%
“…39 Furthermore, several studies identified that AKT1 and CREB1 were associated with synaptic plasticity in the hippocampus. 40 Liu et al identified that PIAS1 has an important role in neuronal plasticity, learning and memory function. 41 Also, CDK2AP1 in the yellow module was recently identified as a susceptibility gene for intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…Three different isoforms of AKT exist. Whereas AKT1 and AKT3 are mainly expressed in neurons, AKT2 is predominantly expressed in astrocytes (Levenga et al, 2017). So far, the exact function of AKT in neurons is not clear, but AKT1 has been implicated in late long term potentiation (Levenga et al, 2017) and AKT3 in neuronal growth (Rivière et al, 2012;Adams et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas AKT1 and AKT3 are mainly expressed in neurons, AKT2 is predominantly expressed in astrocytes (Levenga et al, 2017). So far, the exact function of AKT in neurons is not clear, but AKT1 has been implicated in late long term potentiation (Levenga et al, 2017) and AKT3 in neuronal growth (Rivière et al, 2012;Adams et al, 2016). AKT is activated by phosphatidylinositol 3kinase (PI3K) and the PI3K/AKT signaling pathway is known to reduce apoptosis and promote survival and proliferation (Brunet et al, 1999) and thereby counteracts neuronal cell death (Peltier et al, 2007).…”
Section: Discussionmentioning
confidence: 99%